Raça, sexualidade e política: um estudo da constituição de organizações de lésbicas negras no Rio de Janeiro - Santos, Regina Coeli Benedito dos (2007)
This thesis aimed at examining black lesbian organizations in Rio de Janeiro. We assumed as hypothesis that the building of such organizations was derived from the difficulties in discussing sex and race related themes in two social movements. The feminist movement and the black movement. Data for this research were collected from written (reports, newspapers, pamphlets, etc.) and oral sources (interviews with activists from the feminist, black and black-lesbian movements). The examination of such data confirmed our hypothesis and suggested that black-lesbian diaspora created an important space for constructing new identities.